Analisis Pengendalian Persediaan Bahan Baku Kedelai dengan Metode Economic Order Quantity pada UMKM Tempe Maju Makmur di Karanganyar - Ikhsan Aji Permana; Sunarso (Teewan Journal Solutions, 2025)
Tempe Maju Makmur UMKM in Karanganyar is an UMKM engaged in the food production sector, namely tempeh. Tempe Maju Makmur UMKM in Karanganyar tries to control the cost of raw material inventory with the right raw material control system. The problem in this study is whether the application of the Economic Order Quantity method can make the cost of controlling raw material inventory more efficient at Tempe Maju Makmur UMKM in Karanganyar. The purpose of this study is to analyze the efficiency of the raw material inventory control system at Tempe Maju Makmur UMKM in Karanganyar and to analyze the application of the Economic Order Quantity method in making the cost of controlling raw material inventory more efficient at Tempe Maju Makmur UMKM in Karanganyar. The usefulness of this study as a consideration for Tempe Maju Makmur UMKM in Karanganyar to make the cost of raw material inventory more efficient and can be used to make decisions related to the efficiency of raw material inventory costs. This study uses the Economic Order Quantity method at UMKM Tempe Maju Makmur in Karanganyar. The data required is a general description of UMKM Tempe Maju Makmur in Karanganyar, production process, production quantity data, storage cost data and order cost data at UMKM Tempe Maju Makmur in Karanganyar. Data sources are primary data. Data collection techniques with observation and interviews. Data analysis techniques use quantitative. The results of this study indicate that the raw materials of Tempe Maju Makmur are not optimal. This is evidenced by the total inventory costs incurred in accordance with the policy of UMKM Tempe Maju Makmur in Karanganyar of Rp 3.041.000 which is greater than the total Economic Order Quantity method of Rp 1.873.000. From this comparison, the Economic Order Quantity method produces the most optimal total cost.